Evaluation of the green open space policy of bekasi city in achieving development indicators (sustainable settlements) - Najmuddin Najmuddin; Sucahyanto Muzani Jalaluddin (JURNAL MANAJEMEN, 2019)
The objective of this research was to evaluate the green open space policy of Bekasi City in achieving development indicators (sustainable settlements). It was a qualitative research with evaluation method conducted in the City of Bekasi, West Java in 2018. The data were collected through participant observation using interview, observation, and document study. The data was analysed and interpretated through (1) Data reduction, sorting, concentration and simplification of "rough" data, abstracting, and information that emerge from written records in the field: (2) Display data, try to present data and the whole picture and certain parts of the research; (3) Conclusions and verification, search and find meaning for the data collected by looking for patterns of relationships, similarities, differences and the systems. The findings of the implementation have been carried out but must be revised to adapt the development of the central government, named the National Strategic Project. Green open space in the City of Bekasi will be increased every year to 0.15% in a sustainable manner so that green open space can be consistently distributed throughout the City of Bekasi.